Gene expression of Corynebacterium pseudotuberculosis virulence factors and their role in the pathogenesis of caseous lymphadenitis (Research, Society and Development, 2022)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CL), an infectious, granulomatous, chronic and debilitating disease that affects several animals, including goats, sheep, cattle, horses, camelids and, more rarely, humans. The group called CMNR, composed of bacteria of the genera Corynebacterium, Mycobacterium, Nocardia and Rhodococcus, is involved in several important pathologies, both in human and veterinary medicine. The focus of studies with the etiologic agent of CL has been in relation to diagnosis, epidemiology, prophylaxis, therapy and genomics. Although the disease has been studied since the beginning of the 20th century, similarly to those caused by other bacterial entities, the survey about the pathophysiological and evasion mechanisms of this agent are practically unknown. The virulence factors of the etiologic agent of caseous lymphadenitis are few, but the pioneering sequencing of the genome of a strain isolated from a human patient, Corynebacterium pseudotuberculosis FRC41, allowed the identification and annotation of several protein-coding genes whose physiological characteristics fit definition of virulence factor. In Mycobacterium tuberculosis, PknG kinase controls glutamine metabolism, but it can be secreted into macrophage phagosomes, interfering with the maturation of these organelles. The same enzyme exists in other representatives of the suborder Corynebacterineae, including C. pseudotuberculosis, other antigens have already been described and their are being elucidated. In this context, the objective of this work was to carry out a review about the virulence factors of Corynebacterium pseudotuberculosis.